Beyond Intent: An Empirical Study on the Underlying Factors of Cash Waqf Contribution - Pasaribu, Popy Novita; Kemora, Haura (Jurnal Manajemen (Edisi Elektronik), 2024)
In pursuit of a flourishing Indonesia by 2045 through the productive waqf movement, collaborative efforts are essential to optimize resources and unleash the full potential of waqf. This research delves into the determinants influencing individuals' inclination to contribute to cash waqf, encompassing variables such as religiosity, education, information influence, comfort, trust in waqf institutions, and perceptions of ihsan. Two independent dummy variables, namely the impact of the covid-19 pandemic on cash waqf and pre-pandemic cash waqf participation, are employed to assess whether past waqf behavior influences future intentions. The dependent variable is engagement in cash waqf. Utilizing a purposively distributed questionnaire via Google Form in Jakarta, 107 responses were obtained through snowball sampling. Regression analysis using SPSS 26.0 revealed that comfort, trust in Waqf Institutions, and Ihsan positively impact the interest in participating in cash waqf. Interestingly, the perception of the covid pandemic did not affect the intention to contribute cash waqf, but individuals who had previously participated in cash waqf before the pandemic exhibited a significant likelihood to continue their contributions.